(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
In the North-West Sinis Peninsula (Western Sardinia) a stratigraphic sequence, the Capo Mannu Fm., that evolves from marine-littoral to continental-dunar, is present. A vertebrate fauna is reported within the middle part of this coastal dune complex. These new remains, here referred to as the Capo Mannu D4 Local Fauna, are slightly younger in the sedimentary succession than the Local Fauna known in the literature as Mandriola and here re-named the Capo Mannu D1 Local Fauna. Vertebrates from Capo Mannu D4 include reptiles (Chelonii) and mammals (Bovidae and Suidae). The tortoise fossils show peculiarities of shape that require the naming of a new species. The suid material includes a fragmentary palate and a partial mandible, referable to the endemic species Sus sondaari. Bovids are well represented in the assemblage, although quite fragmentary. They have been identified as belonging to at least two forms. One of these is comparable in morphology to Nesogoral, one of the most characteristic taxa of the Late Pliocene-Early Pleistocene Sardinian endemic fauna (the so called "Nesogoral complex"). On the whole, the Capo Mannu D4 assemblages open a new window on the Plio-Pleistocene terrestrial faunas of the Sardinian Island.